2016
DOI: 10.1175/ei-d-15-0033.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Patterns of Cloud Cover and Fog Inundation in Coastal California: Ecological Implications

Abstract: The presence of low-lying stratocumulus clouds and fog has been known to modify biophysical and ecological properties in coastal California where forests are frequently shaded by low-lying clouds or immersed in fog during otherwise warm and dry summer months. Summer fog and stratus can ameliorate summer drought stress and enhance soil water budgets and often have different spatial and temporal patterns. Here, this study uses remote sensing datasets to characterize the spatial and temporal patterns of cloud cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…2) (Junak 1995). CLCF is most persistent over the four northern Channel Islands from May to September (Rastogi et al 2016).…”
Section: Study Areamentioning
confidence: 99%
“…2) (Junak 1995). CLCF is most persistent over the four northern Channel Islands from May to September (Rastogi et al 2016).…”
Section: Study Areamentioning
confidence: 99%
“…In addition, the cloud base over land rises high enough that a TWI limit to vertical extent of the clouds may result in shallower (thinner) cloud layers at the highest land elevations ( Fig. 6; Rastogi et al, 2016). When topography is close to the ocean this effect is especially pronounced, as seen in the CALIPSO data with the disproportionate effect on the clouds by the lower peak elevation but closer oceanic proximity of the northernmost peninsula of the Dominican Re-public (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…We expected to find cloud base altitudes above the LCL and cloud tops at or below the TWI for tradewind conditions (Brueck et al, 2014;Malkus, 1955); thus, we used the radiosonde profiles to compute values of minimum LCL and maximum TWI base over each day to quantify frequency of stable marine boundary layers and trade-wind cloud conditions at the site (Rastogi et al, 2016;Zhang et al, 2012). The LCL calculation we used involves an air parcel representing the mean potential energy in the lowest 50 hPa of the atmosphere for a mean-layer LCL; this accounts for the fact that the thermodynamic profile of the boundary layer may not be well represented by that of the surface layer (Craven et al, 2002; for details see Appendix A).…”
Section: Radiosonde Data At Airportsmentioning
confidence: 99%
“…Recent studies have shown that fog‐drip captured by island vegetation contributes significantly to the hydrology of the islands, independent from measured precipitation, especially during the dry season from May to September (Fischer, Still, & Williams, ; Rastogi et al, ; Williams, Still, Fischer & Leavitt, ). Historical overgrazing significantly reduced fog‐drip by stripping San Miguel and other Channel Islands of much of their vegetation (Gill, Fauvelle, & Erlandson, ), but the recovery of plant communities following the removal of exotic grazing animals seems to be fueling a recovery of island hydrology.…”
Section: Study Areamentioning
confidence: 99%